2022
DOI: 10.3390/s22228715
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of and Reduction in Noise in Current Measurement of XCP under the Laboratory Condition

Abstract: Expendable current profiler (XCP) is one of the most vital devices detecting ocean currents. Compared with other methods, the expendable feature makes trials with XCP much faster and more hidden, while the accuracy of XCP is considerably influenced by electromagnetic noise all around. Aiming at researching the influence and reducing the noise, this study carried out laboratory simulation experiments. The designed laboratory experiments mainly have a self-developed rotation gear, an XCP prototype, a plastic flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…As outlined in Section II regarding the measurement principle of XCP, electric detection requires the XCP to rotate in water. However, previous experiments revealed that the noise generated by the rotation of an electric machine exceeded the marine current signal [41]. Therefore, this study devised a plan to use the rotation of the electric field instead of XCP.…”
Section: B Velocity Measuring Performances For Marine Currentsmentioning
confidence: 99%
“…As outlined in Section II regarding the measurement principle of XCP, electric detection requires the XCP to rotate in water. However, previous experiments revealed that the noise generated by the rotation of an electric machine exceeded the marine current signal [41]. Therefore, this study devised a plan to use the rotation of the electric field instead of XCP.…”
Section: B Velocity Measuring Performances For Marine Currentsmentioning
confidence: 99%
“…Noise reduction Modern BSCs are made to be quieter, providing laboratory staff with a less disturbing and more comfortable working atmosphere [56].…”
Section: Energy Efficiencymentioning
confidence: 99%